Pengaruh Motivasi Pengetahuan Perpajakan, Motivasi Karir, dan Motivasi Ekonomi Terhadap Minat Mahasiswa Mengikuti Program Brevet Pajak - Selviana; Yudea; Dika Karlinda Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of tax knowledge motivation, career motivation, and economic motivation on students' interest in participating in tax brevet. The population in this study is all students of the accounting study program in Balikpapan who have completed the taxation course. Sampling was conducted using the accidental sampling method with a sample of 276 students. The research method used is a quantitative method using a questionnaire as a research instrument. The data analysis method used in this study is the Partial Least Square-Structure Equation Model (PLS-SEM) using the help of SmartPLS 3.0 software. The results of the study show that the motivation of tax knowledge, career motivation and economic motivation , an effect on students' interest in participating in tax brevet.